Evaluation and usage of the map collection of selected geosciences libraries in Metro Manila - Ramos, Bryan Raymond G.; Timoteo, Christine B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
Maps are essential in facilitating geoscience related activities of students, researchers and professionals. Geosciences libraries provide map collections that can be accessed and retrieved by its users. This study was conceptualized to know the extent of map collection of the target libraries and determine and evaluate how they acquire, organize and disseminate the map collections. The researcher also sought to determine the users of the map collections and know their purposes of using such.
The researcher followed a descriptive type of research to conduct the study. Face-to-face interviews and survey questionnaires were used to gather the data needed.
The researcher determined that the kinds of maps present in the map collections of the selected geosciences libraries in Metro Manila are topographic maps, geologic maps, atmospheric maps, political maps, bathymetric maps, land use maps, agricultural maps, and nautical maps. Maps were acquired through purchases from other map producing institutions and through gifts and donations from other institutions or individuals; while selection of the materials is based on the need of the parent institution to facilitate their activities. The libraries do not adapt a definite classification and cataloging scheme. Catalogs (manual or electronic) and indexes are the main materials utilized by the geosciences libraries to access their map collections. Answering reference questions and interlibrary services are the most common reference services rendered by the respondents. Rules and regulation regarding the loaning of the maps is restrictive to avoid its deterioration. Weeding for the map collection is rarely done. Older maps are kept for they are valuable in comparing changes from the present maps. Excess duplicate maps are ones weeded from the collection, where they are given to other institutions as gifts or donations. Resource sharing of the map collections between libraries does not exist but it is noted that some librarians are initiating to make such endeavor. Students, research assistants, geologists, engineers and employees of the parent institution compose the users of the geosciences libraries. The profile of the users varies from each institution, but most of the users are the employees, students, and geologists. Users of the geosciences libraries utilize the map collection mainly for the purposes of field mapping and research. Users also noted other types of maps that they utilize for their researches and activities that are not present in the map collections of the surveyed geosciences libraries like structural maps, geo-hazard maps, soil maps, forest maps, road maps, population density maps and some digital maps.
Recommendations suggested by the researcher includes widening of the map collection, adapting proper classification and cataloging system, greater demand for support and funding from the libraries' respective parent institutions, establishment of resource sharing system between or among the libraries and further studies regarding developments in map production in the country.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Earth sciences libraries -- Philippines -- Manila Metropolitan Area; Map collections -- Evaluation; Map collections -- Use studies